Disciplinary paternalism and resistance in Ontario’s forensic mental health system - Kennedy, Liam (Critical criminology, 2023)
This manuscript offers a critical intervention in the forensic mental health scholarship. Our analysis of twenty-six appeal case files reveals that the Ontario Review Board (hereafter ORB)-the body responsible for those deemed not criminally responsible on account of mental disorder-engages in processes of normalization expressed paternalistically and extending into life domains that do not directly portend a threat to public safety, most notably employment and housing, personal appearance, and civility. We document how the ORB-in conjunction with the treatment team-governs the subjectivity of some NCR individuals, ambiguously demarcating what qualifies as appropriate insight and motivation. We argue that in some instances the ORB seeks to produce individuals who are self-regulating, self-reliant, and engaged in socially-approved structured activities. Resistance to this disciplinary paternalism is sometimes pathologized, perceived as an indicator of risk. We call for a re-imagining of the forensic mental health system.